SiO2 organic modified binder composite super-hydrophobic antireflection film and preparation method thereof

Through the technical means of SiO2 organic modified binder composite superhydrophobic and amplicon-enhancing film, the problems of surface reflection and dust accumulation of photovoltaic modules are solved, and the effect of improving the light transmittance and hydrophobicity of photovoltaic glass is achieved. It is suitable for photovoltaic modules used outdoors for a long time.

CN119875509APending Publication Date: 2025-04-25ZERO-05 (CHONGQING) NANOTECHNOLOGY CO LTD

Patent Information

Application Number
CN202510069951.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The surface reflection and dust accumulation of existing photovoltaic modules lead to a reduced photovoltaic power generation efficiency, and the adhesion and scratch resistance of traditional superhydrophobic films are insufficient, making it difficult to be suitable for long-term outdoor use.

Method used

A film layer with good adhesion, scratch resistance and light transmittance was prepared by combining SiO2 organically modified binder with a combination of a hydrophobic modified organic binder and a silicon source reaction system.

Benefits of technology

It improves the light transmittance and hydrophobicity of photovoltaic glass, enhances the adhesion and weather resistance of the film layer, and is suitable for photovoltaic modules used outdoors for a long time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005245414550000041
    Figure BDA0005245414550000041
  • Figure BDA0005245414550000071
    Figure BDA0005245414550000071
  • Figure BDA0005245414550000072
    Figure BDA0005245414550000072
Patent Text Reader

Abstract

The invention belongs to the technical field of optical thin film materials, and particularly relates to a SiO2 organic modified binder composite super-hydrophobic antireflection film and a preparation method thereof. The SiO2 organic modified binder composite super-hydrophobic antireflection film is prepared from a hydrophobic modified organic binder and a silicon source reaction system, wherein the silicon source reaction system comprises water, isopropanol, ammonia water, tetraethoxysilane and methyl triethoxysilane. The composite super-hydrophobic antireflection film has good adhesive force, scratch resistance and super-hydrophobicity, the light transmittance and hydrophobicity of photovoltaic glass can be effectively improved by coating the surface of the photovoltaic glass with the composite super-hydrophobic antireflection film, and the composite super-hydrophobic antireflection film has good application prospects in the technical field of optical thin film materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of optical thin film materials, and in particular relates to a SiO2 organic modified binder composite super-hydrophobic anti-reflection film and a preparation method thereof. Background Art

[0002] The surface of photovoltaic modules installed outdoors will lose about 8% of light due to the reflection of the glass itself, and the surface will gradually fall dust, resulting in less and less incident light, which will lead to a gradual decrease in its power generation. In order to deal with this problem, photovoltaic power stations need to regularly organize operation and maintenance personnel to clean the surface of the modules, which wastes a lot of manpower. The glass surface will become rough after repeated friction, resulting in diffuse reflection, which in turn leads to a decrease in the amount of light entering. Coating a layer of hydrophobic self-cleaning anti-reflective coating on the front glass of the module can effectively reduce the reflection of the glass itself and increase the amount of light entering the glass. The hydrophobic properties of the coating make it difficult for dust to adhere to the glass surface, and the dust on the glass surface can be easily removed by rainwater when it rains.

[0003] The hydrophilic / hydrophobic principle refers to: at the interface of solid, liquid and gas, the angle from the solid-liquid interface through the liquid to the gas-liquid interface is called the contact angle. Super-hydrophobic means that when a drop of water falls on a flat object, the contact angle is greater than 150°, the water drop is basically spherical, and basically does not wet the surface of the object; the opposite is super-hydrophilic, which means that the contact angle of the water drop is less than 5°, and the water drop is basically completely flat on the surface of the object. Both super-hydrophilic and super-hydrophobic have a good cleaning effect on the surface of objects. When super-hydrophilic, the water drop can completely wet the surface and take away dust and dirt when it flows down. When super-hydrophobic, the water drop can quickly roll down and take away dirt. The lotus leaves in nature have a layer of biological wax on the surface of the lotus leaves, which have super-hydrophobic function, so they can "come out of the mud without being stained." Traditional super-hydrophobic films are mainly achieved through two aspects: 1. Coating the surface with low surface energy materials; 2. Creating a rough structure on the surface (under the premise that the surface is hydrophobic, the rougher the surface, the more hydrophobic it is; the rougher the surface, the more hydrophobic it is; the hydrophilic surface, the rougher the surface, the more hydrophilic it is).

[0004] The principle of anti-reflection coating is: anti-reflection coating is also called anti-reflection coating. Its main function is to reduce or eliminate the reflected light from optical surfaces such as lenses, prisms, and plane mirrors, thereby increasing the light transmittance of these components. In any optical system, light always passes through a series of light-transmitting surfaces. On the surface of each light-transmitting surface, part of the light is reflected and part of the light is refracted.

[0005] SiO2 is a commonly used anti-reflection film material. The SiO2 sol is prepared by the sol-gel method and coated on the surface of photovoltaic glass. It can effectively increase the transmittance and improve the power generation efficiency of photovoltaic modules.

[0006] The invention patent with announcement number CN115073016B, "A method for preparing a high-transmittance super-hydrophobic anti-reflection film", uses anhydrous ethanol as a solvent, deionized water and tetraethyl orthosilicate as reactants, and ammonia water as an alkaline catalyst, which are added to a reaction bottle in sequence, reacted at a constant temperature, sealed and aged to obtain SiO2 sol; then hexamethyldisilazane is added to the prepared SiO2 sol, reacted at a constant temperature, sealed and aged to obtain a hydrophobically modified SiO2 sol; then the prepared hydrophobically modified SiO2 sol is plated on the surface of a glass substrate by an immersion-pulling method, and dried at room temperature to finally obtain a high-transmittance super-hydrophobic anti-reflection film; a large number of experimental studies have shown that the SiO2 sol obtained by catalysis with ammonia water exists in the form of round particles. When coated into a film, there are fewer binding sites between SiO2 particles and between SiO2 particles and the glass substrate, and the coating has poor bonding strength, which is difficult to be applied to photovoltaic modules used outdoors for a long time.

[0007] Announcement number is CN110272645B invention patent "a kind of super hydrophobic coating that can be recoated and transparent and its preparation method and application", ethanol and chain nano silica sol are mixed to obtain solution A;Ethanol and tetraethyl orthosilicate are mixed, then added ammonia stirring and aged, then tetraethyl orthosilicate is added and stirred to obtain solution B;Solution A and solution B are mixed and stirred to obtain solution C;Add modifier and surfactant to solution C and place to obtain super hydrophobic coating after stirring, after removing water with activated molecular sieve. The coating prepared by this method, chain SiO2 and SiO2 sol obtained by ammonia catalysis are mixed, and the coating adhesion is relatively improved by ammonia catalysis SiO2, but due to two forms of SiO2, it is only physically mixed, not generated by chemical reaction, and observed by actual experiment, the hydrophobic coating adhesion and scratch resistance prepared by the method are poor, and two different forms of SiO2 sol are mixed, which easily leads to system gel. Summary of the invention

[0008] Based on the above technical background, the main purpose of the present invention is to provide a SiO2 organic modified binder composite super hydrophobic anti-reflection film and a preparation method thereof, so as to overcome the deficiencies in the prior art.

[0009] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0010] The first aspect of the present invention is to provide a SiO2 organic modified binder composite super hydrophobic anti-reflection film, wherein the SiO2 organic modified binder composite super hydrophobic anti-reflection film is prepared from a hydrophobically modified organic binder and a silicon source reaction system, wherein the addition amount of the hydrophobically modified organic binder is 1 to 2% of the mass of the silicon source reaction system;

[0011] The silicon source reaction system includes water, isopropanol, ammonia water, tetraethyl orthosilicate (TEOS) and methyltriethoxysilane (MTES), and the mass ratio of water, isopropanol, ammonia water, tetraethyl orthosilicate and methyltriethoxysilane is 1:10.5:(0.01-0.016):(1.2-1.8):(0.1-0.15).

[0012] Preferably, the amount of the hydrophobically modified organic binder added is 1.3-1.5% of the mass of the silicon source reaction system;

[0013] Preferably, in the silicon source reaction system, the mass ratio of water, isopropanol, ammonia water, ethyl orthosilicate and methyltriethoxysilane is 1:10.5:(0.01-0.015):(1.3-1.7):(0.11-0.15).

[0014] Preferably, the hydrophobically modified organic binder is prepared from a polyhydroxy organic binder and a fluorine modifier, and the added amount of the fluorine modifier is 5-15% of the mass of the polyhydroxy organic binder.

[0015] More preferably, the polyhydroxy organic binder is prepared from the following raw materials in parts by weight:

[0016]

[0017] The second aspect of the present invention is to provide a method for preparing the SiO2 organic modified binder composite super hydrophobic antireflection film according to the first aspect of the present invention, the preparation method comprising the following steps:

[0018] Step 1, mixing a hydrophobically modified organic binder, water, isopropanol and ammonia water, stirring after heating, to obtain liquid A; mixing ethyl orthosilicate and methyltriethoxysilane, and ultrasonicating to obtain liquid B; adding liquid B dropwise to liquid A under constant temperature stirring conditions, and after the dropwise addition is completed, reacting at a constant temperature to obtain a reaction product;

[0019] Step 2, reflux the product in the reaction under constant temperature conditions to remove ammonia, and after the ammonia removal is completed, react at a constant temperature under stirring conditions, and then age at room temperature to obtain a SiO2 organic modified binder composite super hydrophobic permeability-enhancing liquid;

[0020] Step 3: coating the SiO2 organic modified binder composite super hydrophobic anti-reflection liquid, and then curing at room temperature to obtain the SiO2 organic modified binder composite super hydrophobic anti-reflection film.

[0021] In step 1,

[0022] Preferably, a hydrophobically modified organic binder, water, isopropanol and aqueous ammonia are mixed, the temperature is raised to 50-70° C., and stirred at a constant temperature for 5-20 minutes to obtain liquid A;

[0023] Preferably, after the ethyl orthosilicate and methyltriethoxysilane are mixed, ultrasonic treatment is performed for 3 to 10 minutes, preferably, after the mixing, ultrasonic treatment is performed for 5 minutes, to obtain liquid B.

[0024] Preferably, under a constant temperature stirring condition of 50 to 70° C., liquid B is added dropwise to liquid A. After the dropwise addition is completed, the mixture is reacted at a constant temperature of 50 to 70° C. for 20 to 45 minutes to obtain a reaction product.

[0025] Preferably, the preparation method of the hydrophobically modified organic binder comprises the following steps:

[0026] Step a, heating butyl acetate to boiling point, passing nitrogen to pressurize, adding uniformly mixed methyl styrene, styrene, acrylic acid, hydroxypropyl acrylate, hydroxyethyl acrylate, butyl acrylate and di-tert-butyl peroxide to butyl acetate, heating to react, then adding butyl acetate and di-tert-butyl peroxide, keeping the temperature, cooling and filtering to obtain a polyhydroxy organic binder;

[0027] Step b, dissolving the polyhydroxy organic binder in ethyl acetate, adding a fluorine modifier, and reacting at a constant temperature under stirring to obtain a hydrophobically modified organic binder.

[0028] More preferably, in step a,

[0029] The mixture is pressurized to 0.2-0.3 MPa with nitrogen, and methyl styrene, styrene, acrylic acid, hydroxypropyl acrylate, hydroxyethyl acrylate, butyl acrylate and di-tert-butyl peroxide, which are uniformly mixed, are added into butyl acetate at a feed rate of 5.5-6.5 g / min, and the temperature is raised to 130-170° C., and the mixture is kept at this temperature for 2-4 hours, and then butyl acetate and di-tert-butyl peroxide are added at once, and the mixture is kept at 130-170° C. for 2-4 hours;

[0030] More preferably, in step b, a fluorine modifier is added, and the temperature is raised to 70-85° C. and reacted at a constant temperature for 20-25 hours under stirring to obtain a hydrophobically modified organic binder.

[0031] In step 2,

[0032] Preferably, the product in the reaction is refluxed at a constant temperature of 70 to 85° C. for 10 to 15 hours, and after reflux to remove ammonia, an acidic solution is added to adjust the pH to 3 to 6. The product is reacted at a constant temperature of 50 to 70° C. for 10 to 20 hours under stirring, and then aged at room temperature for 3 to 5 days.

[0033] The beneficial effects of the present invention are:

[0034] (1) The SiO2 organic modified binder composite super hydrophobic anti-reflection film is prepared from a hydrophobic modified organic binder and a silicon source reaction system, wherein the silicon source reaction system uses TEOS and a small amount of MTES as dual silicon sources. Due to the steric hindrance of the methyl group of MTES, a certain loose structure is generated when the acid catalyzes the synthesis of the SiO2 three-dimensional network structure, which further enhances the anti-reflection effect of the coating without affecting the internal bonding force of the coating. At the same time, the methyl group of MTES is hydrophobic, so that the obtained anti-reflection film has good hydrophobic properties and anti-reflection effects. In addition, the hydrophobic modified organic binder of the present invention has good film-forming properties, so that the composite super hydrophobic anti-reflection film has good adhesion, scratch resistance and transmittance.

[0035] (2) The present invention uses TEOS and MTES as dual silicon sources. The methyl group of MTES is hydrophobic, so that the synthesized SiO2 organic modified binder has a certain hydrophobic property. In addition, the grafted fluorine modifier is added, so that the composite super-hydrophobic anti-reflection film finally has super-hydrophobicity.

[0036] (3) The preparation method of the composite super-hydrophobic anti-reflection film described in the present invention uses tetraethyl orthosilicate (TEOS) and methyltriethoxysilane (MTES) as silicon sources and isopropanol as solvent. Ammonia water is first used as a catalyst to catalytically synthesize SiO2 nanoparticles. During the synthesis of the SiO2 particles, a transparent fluorine-modified organic binder is grafted, and then an acid is added to adjust the pH of the system to a weak acid. At this time, under the acid catalysis, the remaining TEOS and MTES continue to dehydrate and condense into a three-dimensional network structure of SiO2. An acid-base two-step catalytic method is used to synthesize a SiO2 sol with a core-membrane composite structure, so that it has a three-dimensional network structure of acid-catalyzed SiO2, and at the same time has a spherical micro-nano structure of base-catalyzed SiO2, and the two structures are bonded by chemical reaction, so that it itself has good adhesion and anti-reflection rate. The grafted fluorine-modified organic binder itself has excellent film-forming properties, hydrophobic properties and weather resistance, which further improves the overall adhesion, scratch resistance and hydrophobicity of the composite super-hydrophobic anti-reflection film. Coating it on the surface of photovoltaic glass can effectively increase the transmittance and hydrophobicity of the photovoltaic glass. The composite super-hydrophobic anti-reflection film has good application prospects in the field of optical thin film material technology. DETAILED DESCRIPTION

[0037] The present invention will be described in detail below, and the characteristics and advantages of the present invention will become clearer and more distinct with the description.

[0038] The first aspect of the present invention is to provide a SiO2 organic modified binder composite super hydrophobic anti-reflection film, wherein the SiO2 organic modified binder composite super hydrophobic anti-reflection film is prepared from a hydrophobic modified organic binder and a silicon source reaction system, and the addition amount of the hydrophobic modified organic binder is 1 to 2% of the mass of the silicon source reaction system.

[0039] Preferably, the addition amount of the hydrophobically modified organic binder is 1.3-1.5% of the mass of the silicon source reaction system.

[0040] The hydrophobic modified organic binder is prepared from a polyhydroxy organic binder and a fluorine modifier, and the added amount of the fluorine modifier is 5-15% of the mass of the polyhydroxy organic binder.

[0041] Preferably, the added amount of the fluorine modifier is 7-10% of the mass of the polyhydroxy organic binder.

[0042] The polyhydroxy organic binder is prepared from the following raw materials in parts by weight:

[0043]

[0044] Preferably, the polyhydroxy organic binder is prepared from the following raw materials in parts by weight:

[0045]

[0046]

[0047] The fluorine modifier is selected from one or more of perfluorohexylethylene, perfluorodecyltrimethoxysilane, and perfluoro-n-propyl vinyl ether, preferably perfluorohexylethylene or perfluorodecyltrimethoxysilane.

[0048] The silicon source reaction system includes water, isopropanol, ammonia water, tetraethyl orthosilicate (TEOS) and methyltriethoxysilane (MTES), and the mass ratio of water, isopropanol, ammonia water, tetraethyl orthosilicate and methyltriethoxysilane is 1:10.5:(0.01-0.016):(1.2-1.8):(0.1-0.15).

[0049] Preferably, the mass ratio of the water, isopropanol, ammonia water, tetraethyl orthosilicate and methyltriethoxysilane is 1:10.5:(0.01-0.015):(1.3-1.7):(0.11-0.15).

[0050] The second aspect of the present invention is to provide a method for preparing the SiO2 organic modified binder composite super hydrophobic antireflection film according to the first aspect of the present invention, the preparation method comprising the following steps:

[0051] Step 1, mixing a hydrophobically modified organic binder, water, isopropanol and ammonia water, stirring after heating, to obtain liquid A; mixing ethyl orthosilicate and methyltriethoxysilane, and ultrasonicating to obtain liquid B; adding liquid B dropwise to liquid A under constant temperature stirring conditions, and after the dropwise addition is completed, reacting at a constant temperature to obtain a reaction product;

[0052] Step 2, reflux the product in the reaction under constant temperature conditions to remove ammonia, and after the ammonia removal is completed, react at a constant temperature under stirring conditions, and then age at room temperature to obtain a SiO2 organic modified binder composite super hydrophobic permeability-enhancing liquid;

[0053] Step 3: coating the SiO2 organic modified binder composite super hydrophobic anti-reflection liquid, and then curing at room temperature to obtain the SiO2 organic modified binder composite super hydrophobic anti-reflection film.

[0054] The above steps are described in detail below.

[0055] In step 1, a hydrophobically modified organic binder, water, isopropanol and aqueous ammonia are mixed, the temperature is raised to 50-70° C., and the mixture is stirred at a constant temperature for 5-20 minutes to obtain a liquid A.

[0056] Preferably, the temperature is raised to 60° C. and stirred at constant temperature for 10 min to obtain liquid A.

[0057] The ethyl orthosilicate and methyltriethoxysilane are mixed and ultrasonicated for 3 to 10 minutes, preferably for 5 minutes, to obtain liquid B.

[0058] Under constant temperature stirring conditions of 50-70°C, liquid B is added dropwise to liquid A. After the addition is completed, the mixture is reacted at a constant temperature of 50-70°C for 20-45 minutes to obtain a reaction product.

[0059] Preferably, under a constant temperature stirring condition of 60° C., liquid B is added dropwise to liquid A. After the dropwise addition is completed, the mixture is reacted at a constant temperature of 60° C. for 30 minutes to obtain a reaction product.

[0060] According to a preferred embodiment of the present invention, the method for preparing the hydrophobically modified organic binder comprises the following steps:

[0061] Step a, heating butyl acetate to boiling point, passing nitrogen to pressurize, adding uniformly mixed methyl styrene, styrene, acrylic acid, hydroxypropyl acrylate, hydroxyethyl acrylate, butyl acrylate and di-tert-butyl peroxide to butyl acetate, heating to react, then adding butyl acetate and di-tert-butyl peroxide, keeping the temperature, cooling and filtering to obtain a polyhydroxy organic binder;

[0062] Step b, dissolving the polyhydroxy organic binder in ethyl acetate, adding a fluorine modifier, and reacting at a constant temperature under stirring to obtain a hydrophobically modified organic binder.

[0063] Preferably, in step a, nitrogen is passed through and pressurized to 0.2-0.3 MPa, and pressurization can prevent boiling. Methyl styrene, styrene, acrylic acid, hydroxypropyl acrylate, hydroxyethyl acrylate, butyl acrylate and di-tert-butyl peroxide, which are uniformly mixed, are added to butyl acetate at a feed rate of 5.5-6.5 g / min, and the temperature is raised to 130-170° C., and the reaction is carried out at this temperature for 2-4 hours. Then, butyl acetate and di-tert-butyl peroxide are added at one time, and the temperature is kept at 130-170° C. for 2-4 hours. After cooling and filtering, a polyhydroxy organic binder is obtained.

[0064] Preferably, nitrogen is passed through and pressurized to 0.23 MPa, and methyl styrene, styrene, acrylic acid, hydroxypropyl acrylate, hydroxyethyl acrylate, butyl acrylate and di-tert-butyl peroxide, which are uniformly mixed, are added to butyl acetate at a feed rate of 6.01 g / min, and the temperature is raised to 150° C., and the reaction is carried out at this temperature for 3 hours, and then butyl acetate and di-tert-butyl peroxide are added at one time, and the temperature is kept at 150° C. for 3 hours. After cooling and filtering, a polyhydroxy organic binder is obtained.

[0065] In step b, a fluorine modifier is added, and the temperature is raised to 70-85° C. and reacted at a constant temperature for 20-25 hours under stirring to obtain a hydrophobically modified organic binder.

[0066] Preferably, a fluorine modifier is added, and the temperature is raised to 80° C. and reacted at a constant temperature for 24 hours under stirring to obtain a hydrophobically modified organic binder.

[0067] The creativity of the present invention lies in that an organic binder is added during the synthesis of silica particles, so that the synthesized silica particles and the organic binder are chemically bonded during the chemical reaction, so that the raw materials used in the composite super-hydrophobic anti-reflection film finally form a whole, which not only gives the anti-reflection film good binding force, but also prevents the anti-reflection film system from producing gel due to the mixing of different raw materials, thereby affecting the performance of the anti-reflection film. In the prior art, the synthesized SiO2 particles and the resin material are simply mixed, and no chemical reaction occurs. Therefore, the anti-reflection film prepared by the present invention has better binding force than the prior art, and does not produce gel. The anti-reflection film of the present invention has better stability and weather resistance.

[0068] In step 2, the product in the reaction is refluxed at a constant temperature of 70 to 85° C. for 10 to 15 hours to remove the remaining ammonia in the product in the reaction.

[0069] Preferably, the product in the reaction is refluxed at a constant temperature of 80° C. for 12 hours to remove the remaining ammonia in the product in the reaction.

[0070] After removing ammonia, add acidic solution, adjust the pH to 3-6, react at a constant temperature of 50-70°C for 10-20 hours under stirring, and then age at room temperature for 3-5 days.

[0071] Preferably, after removing ammonia, an acidic solution is added to adjust the pH to 4-5, and the reaction is carried out at a constant temperature of 60° C. for 10-15 hours under stirring conditions, and then aged at room temperature for 3-4 days.

[0072] The acidic solution is selected from one of hydrochloric acid, acetic acid and nitric acid. Preferably, the acidic solution is hydrochloric acid or nitric acid.

[0073] In step 3, the coating method is selected from one of spray coating, roller coating and spin coating, preferably spin coating.

[0074] The SiO2 organic modified binder composite super hydrophobic permeability-enhancing liquid is dropped onto the ultra-white glass and then spin-coated. The spin-coating conditions are: spin-coating at 800-1200 rpm, 100-200 rpm, and a spin-coating time of 30-40 s. After spin-coating, it is cured at room temperature for 20-45 min.

[0075] Preferably, the spin coating conditions are: spin coating at 1000 rpm, 150 rpm acceleration, spin coating time of 35 s, and room temperature curing for 30 min after spin coating.

[0076] Example

[0077] The present invention is further described below by specific examples, which are limited to illustrating the present invention but not to limiting the scope of the present invention. The raw materials used in the examples of the present invention were all purchased.

[0078] Example 1

[0079] Preparation of organic binder: 60 parts of butyl acetate are added to the reactor, and after heating to boiling point, nitrogen is passed through and pressurized to 0.23 MPa, 43 parts of methyl styrene, 40 parts of styrene, 0.2 parts of acrylic acid, 25 parts of hydroxypropyl acrylate, 11 parts of hydroxyethyl acrylate, 17 parts of butyl acrylate, and 4 parts of di-tert-butyl peroxide are uniformly fed at a rate of about 6.01 g / min through a peristaltic constant flow pump, and reacted at 150°C for 3 hours. 16 parts of butyl acetate and 4 parts of di-tert-butyl peroxide are added at one time, and after keeping warm for 3 hours, the temperature is lowered, the material is discharged and filtered to obtain a multi-hydroxy transparent organic binder.

[0080] Modification of organic binder: The prepared polyhydroxy organic binder was dissolved in ethyl acetate, and 10% of the binder mass of perfluorohexylethylene was added, and the mixture was reacted at 80° C. for 24 hours under stirring to obtain a transparent hydrophobic modified organic binder.

[0081] Preparation of modified binder grafted SiO2 particles: Accurately weigh ammonia water, water, isopropanol and hydrophobically modified organic binder into a reaction container, stir at 60°C for 10 minutes to obtain liquid A; mix TEOS (tetraethyl orthosilicate) and MTES (methyltriethoxysilane) in a certain proportion, and ultrasonicate for 5 minutes to obtain liquid B. Under constant temperature and stirring at 60°C, liquid B is slowly added dropwise to liquid A. The ratio of the amount of each reactant is: water: isopropanol: TEOS: MTES: ammonia water = 1: 10.5: (1.3-1.6): (0.11-0.14): (0.011-0.015), and the solid mass of the organic binder is 1.5% of the mass of the entire reaction system. After the addition is completed, the reaction is kept at a constant temperature for 30 minutes, and the system is kept at a constant temperature and stirred throughout the process.

[0082] Ammonia removal: Reflux the system at a constant temperature of 80°C for 12 hours to remove the remaining ammonia in the system.

[0083] Acid catalysis: After the ammonia removal is completed, add 0.1 mol / L dilute hydrochloric acid to the system, adjust the pH of the system to about 5, react at a constant temperature of 60°C for 15 hours under stirring conditions, and age at room temperature for 4 days to obtain a SiO2 organic modified binder composite super hydrophobic permeability-enhancing liquid that can be coated.

[0084] Example 2

[0085] Preparation of organic binder: 60 parts of butyl acetate are added to the reactor, and after heating to boiling point, nitrogen is passed through and pressurized to 0.25 MPa, 43 parts of methyl styrene, 40 parts of styrene, 0.2 parts of acrylic acid, 25 parts of hydroxypropyl acrylate, 11 parts of hydroxyethyl acrylate, 17 parts of butyl acrylate, and 4 parts of di-tert-butyl peroxide are uniformly fed at a rate of about 6.01 g / min through a peristaltic constant flow pump, and reacted at 150°C for 3 hours. 16 parts of butyl acetate and 4 parts of di-tert-butyl peroxide are added at one time, and after keeping warm for 3 hours, the temperature is lowered, the material is discharged and filtered to obtain a multi-hydroxy transparent organic binder.

[0086] Modification of organic binder: The prepared polyhydroxy organic binder was dissolved in ethyl acetate, and 7% of the binder mass of perfluorotrimethoxysilane was added, and the mixture was reacted at 80° C. for 24 hours under stirring to obtain a transparent hydrophobic modified organic binder.

[0087] Preparation of modified binder grafted SiO2 particles: Accurately weigh ammonia water, water, isopropanol and hydrophobically modified organic binder into a reaction container, stir at 60°C for 10 minutes to obtain liquid A; mix TEOS and MTES in a certain proportion, and ultrasonicate for 5 minutes to obtain liquid B. Slowly drop liquid B into liquid A under 60°C constant temperature stirring conditions. The ratio of the amount of each reactant is: water: isopropanol: TEOS: MTES: ammonia water = 1: 10.5: (1.4-1.7): (0.12-0.15): (0.01-0.014), and the solid mass of the organic binder is 1.3% of the mass of the entire reaction system. After the addition is completed, the reaction is kept at a constant temperature for 30 minutes, and the system is kept at a constant temperature and stirred throughout the process.

[0088] Ammonia removal: Reflux the system at a constant temperature of 80°C for 12 hours to remove the remaining ammonia in the system.

[0089] Acid catalysis: After the ammonia removal is completed, add 0.15 mol / L of dilute nitric acid to the system, adjust the pH of the system to about 4, react at a constant temperature of 60°C for 10 hours under stirring conditions, and age at room temperature for 3 days to obtain a SiO2 organic modified binder composite super hydrophobic permeability-enhancing liquid that can be coated.

[0090] Example 3

[0091] The ultra-white glass was placed in the center of the stage of the spin coater by using the spin coating process, and the composite super-hydrophobic anti-reflection liquid prepared in Example 1 was dropped onto the ultra-white glass. The glass was spin-coated at an acceleration of 1000 rpm and 150 rpm for 35 s. After completion, the glass was cured at room temperature for 30 min to obtain a SiO2 organic modified binder composite super-hydrophobic anti-reflection coating. The film thickness was measured to be 110 nm to 130 nm.

[0092] The ultra-white glass used is 5cm*5cm in size and 3mm in thickness.

[0093] Example 4

[0094] The ultra-white glass was placed in the center of the stage of the spin coater by using the spin coating process, and the composite super-hydrophobic anti-reflection liquid prepared in Example 2 was dropped onto the ultra-white glass. The ultra-white glass was spin-coated at an acceleration of 1000 rpm and 150 rpm for 35 s. After completion, the ultra-white glass was cured at room temperature for 30 min to obtain the SiO2 organic modified binder composite super-hydrophobic anti-reflection coating. The film thickness was measured to be 103 nm to 127 nm.

[0095] The ultra-white glass used is 5cm*5cm in size and 3mm in thickness.

[0096] Experimental example

[0097] Experimental Example 1 Performance Test

[0098] The performance of the ultra-white glass prepared in Example 3 and Example 4 was tested respectively, and the test results are shown in Table 1. Among them, the transmittance test was tested by spectrophotometry, and the test wavelength range was 380-780nm. The transmittance of the ultra-white glass used in Example 1 and Example 2 was 92.1%; the pencil hardness test method was performed in accordance with the standard GB / T6739-2006. The adhesion test method was carried out in accordance with the IS0 9211-4:201 standard, and a cross-cutting test was performed on the sample coating surface with a cross-cutting device. The cutting edge should be completely smooth, without falling off, and be level 0. The test surface of the water contact angle is the coating surface, and the static water contact angle is tested for 5s. The test of the transmittance attenuation is to carry out a pressure accelerated aging test for 24h under the conditions of 121°C and 100%RH. The transmittance changes before and after the test, that is, the transmittance attenuation △T = (transmittance before the test-transmittance after the test) / transmittance before the test.

[0099] Table 1

[0100] Test items Light transmittance Pencil hardness Adhesion Water contact angle Transmittance attenuation Example 3 95.5% 3H Level 0 151° △T=0.24% Example 4 95.7% 3H Level 0 153° △T=0.31%

[0101] As can be seen from Table 1, compared with ultra-white glass, after coating the super-hydrophobic anti-reflective coating of the present invention, its transmittance increases to 95.5% and 95.7%, indicating that coating the super-hydrophobic anti-reflective coating of the present invention can improve the transmittance of ultra-white glass. After coating the super-hydrophobic anti-reflective coating of the present invention, the hardness of the ultra-white glass can reach 3H, the adhesion can reach level 0, the water contact angle is 151-153°, it has super-hydrophobicity, and the transmittance of the ultra-white glass is attenuated by 0.24%-0.31%.

[0102] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

Claims

1. A SiO2 organic modified binder composite super hydrophobic anti-reflection film, characterized in that: The SiO2 organic modified binder composite super hydrophobic antireflection film is prepared from a hydrophobic modified organic binder and a silicon source reaction system, and the addition amount of the hydrophobic modified organic binder is 1 to 2% of the mass of the silicon source reaction system; The silicon source reaction system includes water, isopropanol, ammonia water, tetraethyl orthosilicate and methyltriethoxysilane, and the mass ratio of water, isopropanol, ammonia water, tetraethyl orthosilicate and methyltriethoxysilane is 1:10.5:(0.01-0.016):(1.2-1.8):(0.1-0.15).

2. The SiO2 organic modified binder composite super hydrophobic antireflection film according to claim 1, characterized in that: The amount of the hydrophobically modified organic binder added is 1.3-1.5% of the mass of the silicon source reaction system; In the silicon source reaction system, the mass ratio of water, isopropanol, ammonia water, ethyl orthosilicate and methyltriethoxysilane is 1:10.5:(0.01-0.015):(1.3-1.7):(0.11-0.15).

3. The SiO2 organic modified binder composite super hydrophobic antireflection film according to claim 1, characterized in that: The hydrophobic modified organic binder is prepared from a polyhydroxy organic binder and a fluorine modifier, and the added amount of the fluorine modifier is 5-15% of the mass of the polyhydroxy organic binder.

4. The SiO2 organic modified binder composite super hydrophobic antireflection film according to claim 3, characterized in that: The polyhydroxy organic binder is prepared from the following raw materials in parts by weight:

5. A method for preparing a SiO2 organic modified binder composite super-hydrophobic anti-reflection film according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: Step 1, mixing a hydrophobically modified organic binder, water, isopropanol and ammonia water, stirring after heating, to obtain liquid A; mixing ethyl orthosilicate and methyltriethoxysilane, and ultrasonicating to obtain liquid B; adding liquid B dropwise to liquid A under constant temperature stirring conditions, and after the dropwise addition is completed, reacting at a constant temperature to obtain a reaction product; Step 2, reflux the product in the reaction under constant temperature conditions to remove ammonia, and after the ammonia removal is completed, react at a constant temperature under stirring conditions, and then age at room temperature to obtain a SiO2 organic modified binder composite super hydrophobic permeability-enhancing liquid; Step 3: coating the SiO2 organic modified binder composite super hydrophobic anti-reflection liquid, and then curing at room temperature to obtain the SiO2 organic modified binder composite super hydrophobic anti-reflection film.

6. The preparation method according to claim 5, characterized in that: In step 1, Mix a hydrophobically modified organic binder, water, isopropanol and aqueous ammonia, raise the temperature to 50-70° C., and stir at the constant temperature for 5-20 minutes to obtain liquid A; The ethyl orthosilicate and methyltriethoxysilane are mixed and ultrasonicated for 3 to 10 minutes, preferably for 5 minutes, to obtain liquid B.

7. The preparation method according to claim 5, characterized in that: In step 1, Under constant temperature stirring conditions of 50-70°C, liquid B is added dropwise to liquid A. After the addition is completed, the mixture is reacted at a constant temperature of 50-70°C for 20-45 minutes to obtain a reaction product.

8. The preparation method according to claim 5, characterized in that: In step 1, the preparation method of the hydrophobically modified organic binder comprises the following steps: Step a, heating butyl acetate to boiling point, passing nitrogen to pressurize, adding uniformly mixed methyl styrene, styrene, acrylic acid, hydroxypropyl acrylate, hydroxyethyl acrylate, butyl acrylate and di-tert-butyl peroxide to butyl acetate, heating to react, then adding butyl acetate and di-tert-butyl peroxide, keeping the temperature, cooling and filtering to obtain a polyhydroxy organic binder; Step b, dissolving the polyhydroxy organic binder in ethyl acetate, adding a fluorine modifier, and reacting at a constant temperature under stirring to obtain a hydrophobically modified organic binder.

9. The preparation method according to claim 8, characterized in that: In step a, The mixture is pressurized to 0.2-0.3 MPa with nitrogen, and methyl styrene, styrene, acrylic acid, hydroxypropyl acrylate, hydroxyethyl acrylate, butyl acrylate and di-tert-butyl peroxide, which are uniformly mixed, are added into butyl acetate at a feed rate of 5.5-6.5 g / min, and the temperature is raised to 130-170° C., and the mixture is kept at this temperature for 2-4 hours, and then butyl acetate and di-tert-butyl peroxide are added at once, and the mixture is kept at 130-170° C. for 2-4 hours; In step b, a fluorine modifier is added, and the temperature is raised to 70-85° C. under stirring and reacted at a constant temperature for 20-25 hours to obtain a hydrophobically modified organic binder.

10. The preparation method according to claim 5, characterized in that: In step 2, The product in the reaction is refluxed at a constant temperature of 70-85°C for 10-15 hours. After reflux to remove ammonia, an acidic solution is added to adjust the pH to 3-6. Under stirring conditions, the reaction is carried out at a constant temperature of 50-70°C for 10-20 hours, and then aged at room temperature for 3-5 days.

Citation Information

Patent Citations

  • A recoatable, anti-reflective superhydrophobic coating, its preparation method and application

    CN110272645B

  • A method for preparing a high-permeability superhydrophobic antireflective membrane

    CN115073016B

Cited By

  • Super-hydrophobic anti-reflection composite optical film for AR glasses as well as preparation method and application of super-hydrophobic anti-reflection composite optical film

    CN121522785A